Incidence and predictors of virological failure among children receiving first-line anti-retroviral treatment in public comprehensive specialized hospitals found in Northeast Ethiopia: a retrospective follow-up study - Estifanos Belay Abebe; Meseret Ekubay Gebregeorgis; Fuad Ahmed Seid; Alemu Birara Zemariam; Tadesse Mamo Dejene; Seteamlak Adane Masresha (Frontiers Media S.A., 2024)
BackgroundDespite anti-retroviral treatment coverage in resource-limited countries being highly appreciated, the occurrence of first-line virological failure remains a priority agenda. Therefore, this study serves as an input for evidence of virological failure among children.ObjectiveThis study aimed to assess the incidence and predictors of virological failure among children receiving first-line anti-retroviral treatment in public comprehensive specialized hospitals found in Northeast Ethiopia through a retrospective follow-up study.MethodsA multicenter institution-based retrospective follow-up study was conducted on the medical records of 481 human immunodeficiency virus (HIV)-infected children who were on first-line anti-retroviral therapy from 1 January 2017 to 31 December 2021. Data were retrieved from 15 May to 15 June 2022 at three public comprehensive specialized hospitals. Study participants were recruited using a simple random sampling technique. STATA-14 was used to analyze the data, which was entered using EpiData version 4.6.2.0. The Kaplan-Meier estimator was used to estimate the survival. Both bivariable and multivariable Cox regression models were fitted to identify predictors. Finally, adjusted hazards ratios (AHRs) with 95% confidence intervals (CIs) were computed, and variables with a P-value of <0.05 were considered statistically significant predictors of virological failure.ResultA total of 481 children records were included in the final analysis, with an observed follow-up period of 16,379 person-months. Among these, 60 (12.47%) had developed virological failure, resulting in an overall incidence density rate of 3.67 (95% CI; 2.84, 4.73) per 1000 person-month observations. The hazards of virological failure (VF) among children were found to be increased by being in recent WHO stages III and IV (AHR = 3.688; 95% CI: 1.449-6.388), poor adherence to anti-retroviral treatment (ART) (AHR = 3.506; 95% CI: 1.711-7.234), and living in a rural environment (AHR = 5.013; 95% CI: 1.958-8.351). Conversely, the hazard of VF was reduced by 60% when the age of caregivers was less than 40 years (AHR = 0.405; 0.003-0.449).Conclusion and recommendationsThe incidence rate of virological failure was relatively high. Living in a rural area, poor adherence to ART, being in a recent advanced WHO clinical stage, and having a caregiver of 40 years of age or older were all independent predictors of virological failure in children. Patients or parents (caregivers) need to be aware of the importance of strictly adhering to treatment regimens to prevent virological failure.